Short-term red wine consumption promotes differential effects on plasma levels of high-density lipoprotein cholesterol, sympathetic activity, and endothelial function in hypercholesterolemic, hypertensive, and healthy subjects - Ana CM Andrade; Fernando HY Cesena; Fernanda M Consolim-Colombo; Silmara R Coimbra; Alexandre M Benjó; Eduardo M Krieger; Protasio Lemos da Luz (Clinics, 2009)
OBJECTIVES: To compare the metabolic, hemodynamic, autonomic, and endothelial responses to short-term red wine consumption in subjects with hypercholesterolemia or arterial hypertension, and healthy controls. METHODS: Subjects with hypercholesterolemia (n=10) or arterial hypertension (n=9), or healthy controls (n=7) were given red wine (250 mL/night) for 15 days. Analyses were performed before and after red wine intake. RESULTS: Red wine significantly increased the plasma levels of HDL-cholesterol in the controls, but not in the other groups. The effects on hemodynamic measurements were mild, non-significantly more prominent in healthy subjects, and exhibited high interindividual variability. Across all participants, mean blood pressure decreased 7 mmHg (p <0.01) and systemic vascular resistance decreased 7% (p = 0.05). Heart rate and cardiac output did not significantly change in any group. Red wine enhanced muscle sympathetic fibular nerve activity in hypercholesterolemic and hypertensive patients, but not in controls. At baseline, brachial artery flow-mediated dilation was impaired in patients with hypercholesterolemia and arterial hypertension; red wine restored the dilation in the hypercholesterolemic group but not in the hypertensive group. CONCLUSIONS: Red wine elicits different metabolic, autonomic, and endothelial responses among individuals with hypercholesterolemia or arterial hypertension and healthy controls. Our findings highlight the need to consider patient characteristics when evaluating the response to red wine.